2006
DOI: 10.1111/j.1460-9592.2006.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized comparison of laryngeal tube and laryngeal mask airway in pediatric patients

Abstract: Insertion success rate is high with both LMA and LT in the age group studied. The airway leak pressure, serving as an estimate to judge quality of airway seal, is higher with the LT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…The LTS is a further development of the LT, which allows the separation of respiratory and alimentary tract. Many studies have reported successful ventilation using the LT or LTS (2–7). Lately, LTS was remodeled into LTS II with following characteristics: a longer shaft, a more pointed tip, and a redesigned distal balloon to better fit esophageal inlet.…”
Section: Introductionmentioning
confidence: 99%
“…The LTS is a further development of the LT, which allows the separation of respiratory and alimentary tract. Many studies have reported successful ventilation using the LT or LTS (2–7). Lately, LTS was remodeled into LTS II with following characteristics: a longer shaft, a more pointed tip, and a redesigned distal balloon to better fit esophageal inlet.…”
Section: Introductionmentioning
confidence: 99%
“…These articles suggest that the success of the Laryngeal Tube Ò on first insertion attempt, sore throat, dysphonia, and rate of gastric insufflation is similar to that of the LMA TM , while leak pressure is higher and the fibreoptic laryngeal view is not as good. 18,19 Most of this information applies to children older than 2 years and/or [10 kg. In smaller children, there are limited data, and the data that exist suggest a high failure rate in children \10 kg.…”
mentioning
confidence: 99%
“…Eine ähnliche Untersuchung wurde von Genzwürker et al ( [14], LoE: 2b) an einem größeren Patientenkollektiv von 60 Kindern durchgeführt. Dabei wurden Kinder im Alter von 2 bis 8 Jahren mit normalem Atemweg im Rahmen von elektiven Allgemeinnarkosen untersucht.…”
Section: Vergleichsstudien Zu Larynxtubus Und Larynxmaskeunclassified
“…Gleichzeitig war die Inzidenz von Halsschmerzen trotz Beachtung eines maximalen Cuff-Drucks von 60 cm H 2 O höher. Insgesamt wird die Anwendung des LT gegenüber der LM von den Autoren dieser Studie favorisiert [14]. Eine wichtige Limitation stellt jedoch das Alter der eingeschlossen Patienten (ab 2 Jahre) dar, sodass keine Aussage zur Anwendbarkeit des LT bei Kindern unter 2 Jahren möglich ist.…”
Section: Vergleichsstudien Zu Larynxtubus Und Larynxmaskeunclassified